Unfolding teaching practices in higher education courses: Cases from school leadership programs. (2022) - Jensen, Ruth; Ottesen, Eli
Abstract: This article provides insight into teaching practices in higher education. The empirical data are from master's programs in educational school leadership at universities in Norway and the United States (California). We employed a case study approach to investigate how teaching practices unfolded at the two sites. The data comprised textual materials and video data from two cases. Using Actor–Network Theory, we identified the key entities (social and material) that constitute the teaching practices. While the entities were fairly similar in the cases, the resulting relationships between them, while appearing distinctive, differed. Insights into how teaching practices unfold can offer valuable knowledge when evaluating existing programs and designing new programs in higher education.